Exactech Opteon Femoral Component Fracture 12 Years after Arthroplasty - Shaun P. Patel; Valentin Antoci; John J. Kadzielski; Mark S. Vrahas (Case Reports in Orthopedics)
Arthroplasty implant fracture is a rare but critical complication that requires difficult revision surgery, often with poor results, patient disability, and significant cost. Several reports show component fracture either at the stem or at the neck interface after a relatively short postoperative course. We report such failure after 12 years, suggesting no safe period after which femoral implant fracture does not occur.